Attrition among Human Immunodeficiency Virus (HIV)- Infected Patients Initiating Antiretroviral Therapy in China, 2003–2010 - Zhu, Hao; Napravnik, Sonia; Eron, Joseph; Cole, Stephen; Ma, Ye; Wohl, David; Dou, Zhihui; Zhang, Yao; Liu, Zhongfu; Zhao, Decai; Cohen, Myron; Zhang, Fujie (PLOS ONE, 2012)
Background Mortality and morbidity from HIV have dramatically decreased in both high- and low-income countries. However, some patients may not benefit from combination antiretroviral therapy (cART) because of inadequate access to HIV care, including attrition after care initiation. Methodology/Principal Findings The study population included all HIV-infected patients receiving cART through the Chinese National Free Antiretroviral Treatment Program from 1 January 2003 to 31 December 2010 (n = 106,542). We evaluated retention in HIV care and used multivariable Cox proportional hazard models to identify independent factors predictive of attrition. The cumulative probability of attrition from cART initiation was 9% at 12 months, 13% at 18 months, 16% at 24 months and 24% at 60 months. A number of factors were associated with attrition, including younger age, male gender, and being single or divorced. Patients with higher CD4 cell counts at cART initiation were more likely to drop out of HIV care. The proportion of patients remaining in HIV care increased in more recent calendar years and among patients who initiated modern cART regimens. Conclusions/Significance Retention in HIV care is essential for optimizing individual and public health outcomes. Attrition, even the degree observed in our study, can lead to premature morbidity and mortality, and possibly affect further transmission of HIV and HIV resistant drug variants. Effective strategies to promote retention in HIV care programs are needed. In China these strategies may include focusing particularly on younger male patients and those with higher CD4 cell counts at therapy initiation.